2013
DOI: 10.1155/2013/329189
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Is Associated with Prolongation of the QTc Interval Duration in Patients with Type 2 Diabetes Mellitus

Abstract: Aims. Aim of the study was to evaluate the effect of smoking on autonomic nervous system (ANS) activity and QTc interval duration in patients with Type 2 diabetes mellitus (T2DM). Methods. A total of 70 patients with T2DM (35 chronic smokers, 35 nonsmokers) treated with oral antidiabetic medications underwent continuous ECG Holter monitoring for 24 hours and analysis of time- and frequency-domain measures of heart rate variability (HRV). HRV over short time was also assessed using the deep breathing test. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
2
7
1
1
Order By: Relevance
“…The results of our study pointed to low educational level of residents in TGRR, with half of the participants being lower than primary school. Furthermore, the results revealed that smoking is an independent risk for diabetes in men as shown earlier [ 32 35 ]. Therefore, it is essential to conduct effective behavioral intervention programs to promote healthy ways of life in citizens, such as peer support on smoking cessation especially for people with lower education level.…”
Section: Discussionsupporting
confidence: 76%
“…The results of our study pointed to low educational level of residents in TGRR, with half of the participants being lower than primary school. Furthermore, the results revealed that smoking is an independent risk for diabetes in men as shown earlier [ 32 35 ]. Therefore, it is essential to conduct effective behavioral intervention programs to promote healthy ways of life in citizens, such as peer support on smoking cessation especially for people with lower education level.…”
Section: Discussionsupporting
confidence: 76%
“…The finding of the present study agreed with previous studies. 18 , 33 , 34 Contrary to the present study, Devi et al, 23 showed that there was no significant difference in QT interval between smokers and non-smokers. In the present study, 9 out of 30 (30%) smokers and 2 out of 30 (6.7%) non-smokers had prolonged QTc interval (>440 ms).…”
Section: Discussioncontrasting
confidence: 87%
“…Accumulating evidences had demonstrated that hyperglycaemia and coexisting confounders in diabetes may promote the increases in QTc interval. Increased QTc interval may be related to cigarette smoking [ 32 ], obesity [ 4 ], nonalcoholic fatty liver disease [ 30 ], hypertension [ 33 ], dyslipidaemia [ 6 ], uric acid (UA) [ 34 ], insulin resistance and its associated hyperinsulinaemia [ 35 ], glycaemic status [ 36 ], coronary artery disease, carotid intima media thickness, diabetic neuropathy, diabetic retinopathy, and diabetic cardiomyopathy [ 1 , 9 , 37 ]. In the present study, hypertension, UA and nonmodifiable factors including age and sex were observed to be independently associated with increased QTc interval.…”
Section: Discussionmentioning
confidence: 99%